Islamisasi Selayar Abad XV: Kajian Naskah - Husnul Fahimah Ilyas (Jurnal Lektur Keagamaan, 2014)
The Islamization process taking place at the local level gives wider opportunity to the scientists, especially the historians to conduct research, including the focus of the current research oriented on the history of Islamization. The primary source of the research is derived from manuscript. The problem issued is when did the Islamization process Selayar start? The result of the research shows that the Islamization process institutionally occurred in 1605 in Selayar based on the studies of manuscripts and documents carried out. The process of Islamization did not happen instantly, but it was begun through the previous contiguity of Islam by observing two things. Firstly, the location of Selayar Island was very strategic to become the sea trade routes and the transit for traders who were going to sail to Maluku and the surrounding. Secondly, Selayar had been under the realm of Bone kingdom, Ternate, and Gowa. As the result, the dynamic interrelationship, fluctuating, and mutual influential occurred among the political forces for the next process.Keywords: Islamization, manuscripts, Dato ri Bandang, Selayar